The Classroom Management Approach in the Grammar Practice Class - Anis Firdatul Rochma; Sutrisna Wibawa; Basikin Basikin (Journal of English Language Teaching and Linguistics, 2020)
The grammatical competence is a capacity that is considered necessary to organize words and sentences accurately. Since the teaching of grammar means training the students to improve their communicative competence as well, thus it requires a great deal of time. Although the adequate grammar learning classrooms have been managed, yet the additional grammar practice class is considered necessary to carry out. A number of studies related to traditional and modern grammar learning activities have been conducted. However, there are only a few interests on the classroom management approaches utilized in the grammar practice class. Hence, this study is conducted to analyze the systems, structures, and expectations of the grammar practice class conducted by the English Department at a university in Indonesia. The four primary approaches of classroom management are selected as the main framework in this study. The case study research is chosen to portray the structure of grammar practice class to reveal a particular classroom management approach employed in this program. The process of data analysis discloses that the grammar practice class utilizes the assertive discipline. As a result, the grammar instructor is likely to be classroom leader to create a systematic classroom management.